Hubungan Empati dengan Intensitas Perilaku Merokok di Tempat Umum - Sulastri, Tri; Thalib, Syamsul Bachri; Nurhidayat, Muh. (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2021)
Smoking is a bad habit that can have a negative impact on health, both for smokers and other individuals who are around them or passive smokers. This study aims to explore the relationship between the level of empathy possessed by smokers and the intensity of smoking behavior carried out in public places. The subjects in this study were 349 students in Makassar City. This study uses a quantitative approach, which is carried out by collecting responses from participants using research instruments in the form of smoking behavior questionnaires and empathy scales. Research data from respondents were analyzed using the Pearson Product Moment correlation test. The results of the analysis of the data collected showed a correlation coefficient value of -0.232 and a significance value of 0.000 (p <0.05). These results indicate that there is a significant relationship between empathy and the intensity of smoking behavior in public places in students in Makassar. The higher the empathy possessed by students, the lower the intensity of students to smoke in public places.